Identifikasi Potensi Tingkat Kerusakan Gempabumi Berdasarkan Indeks Kerentanan Seismik Menggunakan Metode Hvsr di Kecamatan Kadia Kota Kendari - La Hamimu Hamimu; Abdul Manan; Risky Ramadhani (Program Studi Teknik Geofisika FITK UHO, 2023)
This research was conducted to identify the potential level of earthquake damage in Kadia District, Kendari City. The potential level of damage is known based on the seismic vulnerability index parameter. The data used is microtremor data obtained from the results of the frequency filtering process of ground vibration data using a Band Pass Filter type with a frequency range of 1.00 to 25.00 Hz. While the ground vibration data was obtained from the results of direct measurements in the field at 16 measurement points using 1 set of portable seismograph TDL 303S. Furthermore, the data is processed using the Horizontal to Vertical Spectral Ratio (HVSR) method to produce the dominant frequency of the soil and the amplification factor used to calculate the seismic vulnerability index. From the results of data processing carried out scientifically in Kadia District, Kendari City, a seismic vulnerability index value was obtained with values ranging from 0.761 to 5.292 /cm. Based on the results of mapping of the potential level of earthquake damage obtained from the results of the seismic vulnerability index value, it shows that Kadia District, Kendari City has a low to moderate potential for damage due to earthquakes. Low zones with seismic vulnerability index values ​​< 3 are scattered in Kadia, Bende, Anaiwoi, and Wowawanggu Villages. Moderate zones with seismic vulnerability index values ​​< 3 to 6 are scattered in Kadia, Pondambea, and Bende Villages.